Insulated wire and method for producing the same
By adding hydrothermal treatment of carnation soil, polyethylene oxide and calcium caramel to the vinyl chloride resin composition and performing electron beam cross-linking treatment, the performance degradation of the conductive wire insulating layer under thinning is solved, and the effect of high extrusion performance and long-term thermal stability is achieved.
Patent Information
- Application Number
- JP2025029657
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-05-02
AI Technical Summary
When the existing vinyl chloride resin composition thins the thickness of the insulating layer, it is difficult to improve the conductivity and long-term thermal stability of the conductive wires at the same time, and the addition of plasticizers will affect its fire protection and electrical performance.
The vinyl chloride resin composition containing 4% or more hydrothermal treatment, 0.03% or more polyethylene oxide and calcium laurate, 0.1% or more phenolic antioxidants, plasticizers and trimethacrylic trimethacrylate (TMPT) and crosslinking is performed by electron beam irradiation.
The extrusion performance and long-term thermal stability of the insulating layer are significantly improved, while maintaining good fire protection and electrical performance.
Smart Images

Figure 2025071345000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vinyl chloride resin composition, an insulated wire using the same, and a method for producing the same. [Background technology]
[0002] There is a technique of adding surface-treated hydrotalcites to vinyl chloride polymers as a stabilizer for improving the stability of vinyl chloride polymers against heat and light (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-40614 A Summary of the Invention [Problem to be solved by the invention]
[0004] For example, insulated wires used for internal wiring of electronic devices, there is a need to reduce the thickness of the insulating layer covering the conductor from the viewpoint of miniaturization and weight reduction of electronic devices. A vinyl chloride resin composition is used as a covering material for insulated wires. Vinyl chloride resin (polyvinyl chloride; PVC) contains chlorine, which is a halogen, in its chemical structure, and vinyl chloride resin alone has high flame retardancy. Since vinyl chloride resin is hard, when it is used as a covering material for electric wires, a plasticizer for softening the vinyl chloride resin composition is added to the base polymer of the vinyl chloride resin. However, due to the influence of additives such as plasticizers, the properties of the vinyl chloride resin composition (e.g., flame retardancy, heat deformation properties, electrical properties, extrusion linear speed during coating processing of electric wires, heat resistance, etc.) may change and the properties may deteriorate. The present inventors have studied the improvement of the properties of vinyl chloride resin compositions, particularly vinyl chloride resin compositions that are particularly suitable when used as a covering material for electric wires.
[0005] An object of the present invention is to provide an insulated wire capable of improving the extrusion molding characteristics and long-run heat resistance of an insulating layer, and a method for producing the same. [Means for solving the problem]
[0006] An insulated wire according to one embodiment has a conductor and an insulating layer covering the conductor, and the insulating layer contains, relative to 100 parts by mass of polyvinyl chloride, 4 parts by mass or more of hydrotalcite, 0.03 parts by mass or more of oxidized polyethylene and / or calcium laurate, 0.1 parts by mass or more of a phenolic antioxidant, a plasticizer, and TMPT (trimethylolpropane triacrylate), the phenolic antioxidant includes a phenolic antioxidant added to the plasticizer, and a value obtained by dividing the amount of the phenolic antioxidant added by the amount of the TMPT (trimethylolpropane triacrylate) added is 0.02 or less.
[0007] In another embodiment, a method for producing an insulated wire having a conductor and an insulating layer covering the conductor includes the steps of: preparing a polyvinyl chloride resin composition containing, relative to 100 parts by mass of polyvinyl chloride, 4 parts by mass or more of hydrotalcite, 0.03 parts by mass or more of polyethylene oxide and / or calcium laurate, 0.1 part by mass or more of a phenolic antioxidant, a plasticizer, and TMPT (trimethylolpropane triacrylate), wherein the phenolic antioxidant includes a phenolic antioxidant added to the plasticizer, and a value obtained by dividing the amount of the phenolic antioxidant added by the amount of TMPT (trimethylolpropane triacrylate) added is 0.02 or less; extruding the polyvinyl chloride resin composition to form the insulating layer; and irradiating the insulating layer with an electron beam to crosslink the polyvinyl chloride resin composition. Effect of the Invention
[0008] According to a representative embodiment of the present invention, the extrusion molding characteristics and long-run heat resistance of the insulating layer can be improved. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing a structural example of an electric wire according to an embodiment; [Diagram 2] 2 is a cross-sectional view showing an example of the structure of a cable including the electric wire shown in FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0011] <Examples of basic wire and cable structures> Fig. 1 is a cross-sectional view showing an example of the structure of an electric wire according to an embodiment, and Fig. 2 is a cross-sectional view showing an example of the structure of a cable including the electric wire shown in Fig. 1.
[0012] An electric wire (insulated electric wire) 10 shown in Fig. 1 has a conductor 11 and an insulating layer 12 that covers the conductor 11. The electric wire 10 is an insulated electric wire. The insulating layer 12 is, for example, cross-linked. The electric wire 10 can be called a cross-linked insulated electric wire.
[0013] The cable 20 shown in Fig. 2 has a plurality of electric wires 10 and a sheath (insulating layer) 21 that collectively covers the plurality of electric wires 10. In the example shown in Fig. 2, the sheath 21 covers two electric wires 10. However, the number of electric wires 10 in the sheath 21 is not limited to two, and may be, for example, three or more. As shown in Fig. 2, it is preferable that all electric wires covered by the sheath 21 are electric wires 10, but as a modified example, an electric wire having a structure different from that of the electric wire 10 may be covered by the sheath 21 together with the electric wire 10.
[0014] Further, in the following, a vinyl chloride resin composition will be described as a material for the insulating layer 12, but the vinyl chloride resin composition described below can also be used as a material for the sheath 21 shown in FIG.
[0015] <Vinyl chloride resin composition> The inventors of the present application have been working to improve the properties of vinyl chloride resin compositions that are particularly suitable for use as an insulating layer for insulated electric wires. In the following embodiment, a technique for improving the properties of vinyl chloride resin compositions obtained by adding additives to vinyl chloride resin as a base polymer will be described. Hereinafter, a vinyl chloride resin composition used in the insulating layer 12 of the electric wire 10 shown in FIG. 1 will be described. With respect to the electric wire 10 used for the internal wiring of electronic devices, there is an increasing need for a thin-diameter electric wire in which the insulating layer 12 covering the conductor 11 is thinned in terms of making the electronic devices more compact or lighter. When a plasticizer is added to improve the processability of vinyl chloride resin, the properties of the vinyl chloride resin composition change. For example, the flame retardancy of the vinyl chloride resin composition is more likely to decrease than that of vinyl chloride resin alone. In addition, for example, the electrical properties (such as insulation properties and properties related to electrical noise) or the heat deformation properties of the vinyl chloride resin composition may decrease compared to vinyl chloride resin alone. In particular, when the covering thickness of the insulating layer 12 is to be thinned, a semi-rigid vinyl chloride resin composition with a reduced amount of plasticizer added may be used. In this case, compared with a soft vinyl chloride resin composition to which a sufficient amount of plasticizer has been added, the extrusion molding characteristics of the coating material, particularly the stability of the outer diameter dimension, long-run heat resistance (no burning (carbonization) occurs when extrusion molding is performed continuously under the specified conditions described in the Examples), or the linear speed during extrusion molding, are likely to decrease. In addition, when an insulating layer made of a semi-rigid vinyl chloride resin composition is crosslinked by irradiating it with an electron beam, the degree of crosslinking tends to be suppressed.
[0016] Therefore, the present inventors have investigated vinyl chloride resin compositions that can improve the extrusion molding characteristics and long-run heat resistance of the insulating layer 12 when the coating thickness of the insulating layer 12 is reduced.
[0017] The vinyl chloride resin composition constituting the insulating layer 12 shown in FIG. 1 includes (A) polyvinyl chloride (vinyl chloride resin) as a base polymer, (D) hydrotalcite, and (E) polyethylene oxide and calcium laurate. More specifically, it includes 4 parts by mass or more of hydrotalcite and 0.03 parts by mass or more of polyethylene oxide and calcium laurate in total per 100 parts by mass of polyvinyl chloride. In addition, it is preferable that the vinyl chloride resin composition constituting the insulating layer 12 further includes 0.1 parts by mass or more of (C) phenolic antioxidant and (F) plasticizer per 100 parts by mass of polyvinyl chloride. The (C) phenolic antioxidant includes a phenolic antioxidant added to the (F) plasticizer, and the value obtained by dividing the amount of the phenolic antioxidant by the amount of TMPT (trimethylolpropane triacrylate) added is 0.02 or less. In addition, it is preferable that the composition further includes 1 part by mass or more of (B) stearic acid-based metal soap in total per 100 parts by mass of polyvinyl chloride.
[0018] [Base polymer] The vinyl chloride resin composition of the present embodiment includes polyvinyl chloride (A) as a base polymer. One or more polyvinyl chlorides having a K value of 71.6 or more can be selected and used as the base polymer. The K value is a value measured by a test method specified in JIS K7367-2 or ISO 1628-2. The K value can be used as an index of the degree of polymerization. When the vinyl chloride resin composition is crosslinked by irradiating with an electron beam, it is preferable to use one having a K value of 75.7 or more and 78.1 or less, rather than using one having a K value of 71.6 alone, from the viewpoint of providing a likelihood of heat resistance and heat deformation characteristics after irradiation with an electron beam.
[0019] [Flame retardant] As the flame retardant, antimony trioxide, aluminum hydroxide, bromine-based flame retardant, amorphous silica, etc. are added. In addition, the above-mentioned (D) hydrotalcite also functions as a flame retardant. When a large amount of aluminum hydroxide is added as a flame retardant, the heat resistance of the vinyl chloride resin composition decreases. By adding hydrotalcite that functions as a flame retardant and a hydrogen chloride scavenger, both heat resistance and flame retardancy can be achieved. As described above, the amount of hydrotalcite added is preferably 4 parts by mass or more when polyvinyl chloride is 100 parts by mass. This allows the vinyl chloride resin composition to have long-run heat resistance. In addition, by adding 4 parts by mass or more of hydrotalcite, the pressure resistance of the vinyl chloride resin composition after crosslinking treatment by electron beam irradiation can be improved. Although details will be described later, according to the results of experimental evaluation by the inventor of the present application, by adding 4 parts by mass or more of hydrotalcite, an insulating layer 12 having insulation voltage resistance performance against a spark voltage of 6000 V can be obtained during extrusion molding and after irradiation of electron beams for crosslinking. Furthermore, by adding 4 parts by mass or more of hydrotalcite, the long-run heat resistance of the vinyl chloride resin composition can be improved.
[0020] It should be noted that as the amount of hydrotalcite added increases, the lubricity of the vinyl chloride resin composition increases. Although the increase in lubricity can be suppressed by increasing the amount of (E) polyethylene oxide and calcium laurate added, from the viewpoint of the electrical properties of the vinyl chloride resin composition (and the viewpoint of raw material costs), it is preferable that the amount of polyethylene oxide and calcium laurate added is 1 part by mass or less per 100 parts by mass of polyvinyl chloride. Therefore, it is preferable that the amount of hydrotalcite added is less than 10 parts by mass per 100 parts by mass of polyvinyl chloride.
[0021] On the other hand, from the viewpoint of decreasing the lubricity of the vinyl chloride resin composition to which 4 parts by mass or more of hydrotalcite is added, the sum of the amounts of (E) polyethylene oxide and calcium laurate added must be 0.03 parts by mass or more when polyvinyl chloride is taken as 100 parts by mass. By making the sum of the amounts of (E) polyethylene oxide and calcium laurate added 0.03 parts by mass or more, the thickness uniformity when the polyvinyl chloride resin composition is molded into the insulating layer 12 can be improved. Details will be described later, but for example, according to the results of experimental evaluation by the inventor of the present application, when the linear speed during extrusion molding is set to 200 m / min, the maximum error of the coating thickness of the insulating layer 12 set to 0.1 mm to 0.2 mm can be made 30 μm or less. In addition, the sum of the amounts of polyethylene oxide and calcium laurate added is preferably 0.6 parts by mass or less.
[0022] [Stabilizer] When the dehydrochlorination reaction is accelerated by the flame retardant, the vinyl chloride resin composition may discolor when irradiated with an electron beam as a crosslinking treatment. For this reason, a stabilizer is added to suppress discoloration of the vinyl chloride resin composition due to irradiation with an electron beam. The stabilizer includes (B) a stearic acid-based metal soap. Examples of the stearic acid-based metal soap include zinc stearate, calcium stearate, magnesium stearate, and stearyl benzoylmethane. As described above, the amount of the stearic acid-based metal soap added is 1 part by mass or more in total when the polyvinyl chloride is taken as 100 parts by mass. The amount of the stearic acid-based metal soap added is preferably 1.5 parts by mass or less in total when the polyvinyl chloride is taken as 100 parts by mass.
[0023] [Plasticizer] (F) The plasticizer is not particularly limited, and known plasticizers can be used. However, it is preferable to use trimellitate-based plasticizers. Examples of trimellitate-based plasticizers include tri-2-ethylhexyl trimellitate, tri-normal alkyl trimellitate, triisononyl trimellitate, and isodecyl trimellitate. In the examples described below, TOTM (tri-normal alkyl trimellitate) (Trimex N-08 manufactured by Kao Corporation: phenolic antioxidant amount 0.5% by mass) or TINTM (isononyl trimellitate) (manufactured by UPC Corporation: phenolic antioxidant amount 0.35% by mass) was used, but other trimellitic acid esters can be used by adjusting the irradiation intensity and the amount of addition during the crosslinking treatment.
[0024] [Other additives] The vinyl chloride resin composition of the present embodiment contains a phenol-based antioxidant (C) as an antioxidant. Examples of the phenol-based antioxidant include 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3-(3,5-di-tert-butyl-4-hydroxyphenyl)stearyl propionate, and 4,4'-butylidenebis-(6-tert-butyl-3-methylphenol). When polyvinyl chloride is taken as 100 parts by mass, the amount of the phenol-based antioxidant added is preferably 0.15 parts by mass or less.
[0025] In addition to the above-mentioned base polymer and each additive, lubricants, colorants, fillers, processing aids, UV absorbers, light stabilizers, crosslinking aids, and other modifiers may be used in combination as necessary. Examples of lubricants include magnesium stearate, which is a metal soap type, stearic acid, which is a fatty acid type, silicone, fatty acid amide type, hydrocarbon type, ester type, and alcohol type. The above-mentioned (E) polyethylene oxide and calcium laurate function as processing aids. Examples of fillers include carbon, clay (including calcined clay), zinc oxide, tin oxide, titanium oxide, magnesium oxide, molybdenum oxide, silicon compounds, quartz, calcium carbonate, magnesium carbonate, and white carbon.
[0026] Examples of the crosslinking aid include trimethylolpropane trimethacrylate (TMPT), triallyl isocyanurate, dipentaerythritol hexaacrylate, triallyl cyanurate, N,N'-metaphenylene bismaleimide, ethylene glycol dimethacrylate, zinc acrylate, and zinc methacrylate.
[0027] Among the above-mentioned cross-linking aids, the addition of TMPT provides the following advantages. For this reason, the vinyl chloride resin composition of the present embodiment preferably contains TMPT. TMPT is an acrylate monomer with three functional groups. When irradiated with an electron beam, TMPT itself bonds between polyvinyl chloride molecules to form a cross-linked structure, making it effective as a cross-linking aid. TMPT is a highly reactive monomer, so this reaction occurs even at low doses.
[0028] As described above, the value obtained by dividing the amount of the phenolic antioxidant by the amount of TMPT (trimethylolpropane triacrylate) added must be 0.02 or less. By adding a phenolic antioxidant, it is possible to suppress the deterioration of the vinyl chloride resin caused by electron beam irradiation. However, the phenolic antioxidant acts as a crosslinking inhibitor because it captures and stabilizes the radical site that is the starting point of the crosslinking reaction of TMPT. By setting the ratio of the phenolic antioxidant to the amount of TMPT added to 0.02 or less, it is possible to adjust the degree of crosslinking without deteriorating performance. It is preferable that the ratio of the phenolic antioxidant to the amount of TMPT added is 0.01 or more.
[0029] In addition, although details will be described later, when a cross-linking test is performed by irradiating the insulating layer 12 shown in Fig. 1 with an electron beam, it is preferable that the thickness of the insulating layer 12 covering the conductor 11 is 0.2 mm or less, and the insulating layer 12 is cross-linked by irradiating an electron beam with an intensity of 5 Mrad or less. This can improve the heat resistance in the evaluation of the insulating layer 12.
[0030] In addition, it is preferable that the insulating layer 12 further contains calcined clay and a clay having a higher SiO2 content than the Al2O3 content. By using the calcined clay and the clay having a higher SiO2 content than the Al2O3 content in combination, the anionic electrolyte supplementation ability is increased. As a result, the electrical characteristics can be improved.
[0031] The insulating layer 12 further contains a black processing pigment, and the black processing pigment preferably contains diisononyl phthalate (DINP), which promotes plasticization when kneading the vinyl chloride resin composition, thereby improving moldability.
[0032] <Evaluation> Next, several examples of the electric wire 10 shown in Fig. 1 and comparative examples for the examples were prepared, and the results of evaluation of each are described. Table 1 shows the blending ratios and evaluation results of Examples 1 to 6. Table 2 shows the blending ratios and evaluation results of Examples 7 to 12. Table 3 shows the blending ratios and evaluation results of Comparative Examples 1 to 6.
[0033] Each of the examples shown in Tables 1 and 2 and the comparative examples shown in Table 3 was manufactured to have the same structure as the electric wire 10 shown in FIG. 1 by the following procedure. The conductor 11 is, for example, a tin-plated conductor in which a tin-plated soft copper wire having an outer diameter of 0.127 mmφ is used as an element wire, and seven element wires are twisted together. The diameter of the conductor 11 is, for example, 0.38 mm. For the insulating layer 12, the composition shown in Tables 1 to 3 was kneaded in an open roll mixer heated to 170°C and pelletized in a granulator to obtain a vinyl chloride resin composition. Then, the obtained vinyl chloride resin composition was used as a raw material and extrusion molding was performed using an extruder to cover the conductor 11. The thickness (covering thickness) of the insulating layer 12 made of the vinyl chloride resin composition was, for example, 0.1 mm. The extrusion molding conditions were, for example, a cylinder temperature of 170°C, a head temperature of 180°C, and the extrusion molding process was performed at a linear speed of 300 m / min. Then, the obtained electric wire 10 was irradiated with an electron beam to perform a crosslinking process. The dose of the electron beam was set to 3.5 Mrad. Examples in which the coating thickness of the insulating layer 12 and the conditions for the electron beam irradiation were changed will be described later.
[0034] Among the evaluation items in Tables 1 to 3, the item "stability of outer diameter dimension during high-speed extrusion" was evaluated as follows. That is, extrusion molding was performed at a linear speed of 300 m / min, and the electric wire 10 was sampled after 5 minutes, 30 minutes, and 60 minutes, and the diameters of four points on the cross section of the electric wire 10 were measured using a microscope. Among the four diameter measurements after 5 minutes, 30 minutes, and 60 minutes, those in which the difference between the maximum and minimum values was within 30 μm were evaluated as ◯, and those in which any one of them exceeded 30 μm were evaluated as ×.
[0035] Among the evaluation items in Tables 1 to 3, the item "heat resistance during extrusion" was evaluated as follows: That is, when extrusion molding was performed continuously for 60 minutes at a linear speed of 300 m / min, if the following three conditions were satisfied: no burning (char) was observed, no foaming was observed in the insulating layer 12, and no adhesion of char was observed around the breaker plate after the extruder was disassembled, the evaluation was ◯; if any one of the above three conditions was not satisfied, the evaluation was ×.
[0036] Among the evaluation items in Tables 1 to 3, the item "voltage resistance during extrusion / after electron beam irradiation" was evaluated as follows. That is, for evaluation during extrusion, a voltage resistance (dielectric strength) test was performed using a spark tester charged at 6000 V while molding was being performed using an extrusion molding machine. For evaluation after electron beam irradiation, a voltage resistance (dielectric strength) test was similarly performed using a spark tester charged at 6000 V for the electric wire 10 in which the insulating layer 12 was crosslinked by irradiating with an electron beam. A sample in which no conduction due to sparks was confirmed was evaluated as ◯. A sample in which conduction due to sparks was confirmed was evaluated as ×.
[0037] Among the evaluation items in Tables 1 to 3, the item "degree of crosslinking" was evaluated as follows. That is, the insulating layer 12 was removed from the electric wire 10 after irradiation with the electron beam, and the gel fraction was measured using this as a sample. Tetrahydrofuran was used as the solvent, and extraction was performed by immersing the sample in the solvent at 70°C for 24 hours. The weights of the sample before and after extraction were measured, and the gel fraction was calculated as weight after extraction / weight before extraction x 100. A calculated gel fraction value of 50% or more was evaluated as ◯, and a value of less than 50% was evaluated as x.
[0038] Among the raw materials shown in Tables 1 to 3, Insulite LHM-103HP manufactured by Mizusawa Industrial Chemicals was used as the SiO2-rich surface-treated clay. The black processed pigment (MXE9749 black) is a processed pigment containing 20 to 45% carbon, PVC, DINP, and a dispersant. The black processed pigment (EP4715 black) is a processed pigment containing 10 to 40% carbon, and containing plasticizers other than PVC and DINP, and other additives.
[0039] [Table 1]
[0040] [Table 2]
[0041] [Table 3]
[0042] As shown in Tables 1 and 2, the vinyl chloride resin composition constituting the insulating layer of the insulated wire of Examples 1 to 12 contains, as its raw materials, (A) polyvinyl chloride (vinyl chloride resin) as a base polymer, (B) stearic acid-based metal soap, (C) phenolic antioxidant, (D) hydrotalcite, (E) polyethylene oxide and calcium laurate, and (F) plasticizer. More specifically, per 100 parts by mass of polyvinyl chloride, the composition contains a total of 1 part by mass or more of stearic acid-based metal soap, 0.1 parts by mass or more of phenolic antioxidant, 4 parts by mass or more of hydrotalcite, a total of 0.03 parts by mass or more of polyethylene oxide and calcium laurate, and a plasticizer. The (C) phenolic antioxidant includes a phenolic antioxidant added to the (F) plasticizer. The value obtained by dividing the amount of the phenolic antioxidant added by the amount of TMPT (trimethylolpropane triacrylate) added is 0.02 or less.
[0043] As shown in Comparative Examples 1 to 4 in Table 3, when the value obtained by dividing the amount of the phenol-based antioxidant added by the amount of TMPT (trimethylolpropane triacrylate) added exceeded the value, the degree of crosslinking was evaluated as ×.
[0044] As shown in Comparative Examples 1, 4, and 5 in Table 3, when the amount of hydrotalcite added was less than 4 parts by mass, the heat resistance during extrusion was evaluated as ×.
[0045] In addition, as shown in Examples 1 to 12 in Tables 1 and 2 and Comparative Examples 1 to 5 in Table 3, by setting the total amount of polyethylene oxide and calcium laurate added to 0.03 parts by mass or more, the stability of the outer diameter dimension during high-speed extrusion can be evaluated as ◯. It is believed that this is because the internal lubricity of the mixture is improved, and a more stable supply state is obtained within the extruder, especially in the metering zone, leading to the stabilization of the outer diameter dimension.
[0046] Next, the relationship between the processing conditions for the insulating layer 12 of the electric wire 10 shown in FIG. 1 and each of the above-mentioned evaluation items will be described. Table 4 is a table showing the relationship between the processing conditions for the insulating layer of the insulated electric wire and the evaluation results of its characteristics. The composition of each example shown in Table 4 was the same as that of Example 3 shown in Table 1. In each example shown in Table 4, the coating thickness of the insulating layer and the irradiation amount when irradiating with electron beams were changed and tests were performed. In addition, in the item "heat aging test" shown in Table 4, evaluation was performed as follows. That is, after irradiating with electron beams, the vinyl chloride resin composition constituting the insulating layer of the electric wire was heated under conditions of maintaining it at 136 ° C for 168 hours, and the change in the elongation rate of the vinyl chloride resin composition before and after heating was evaluated. The elongation rate after heating of 65% or more relative to the elongation rate before heating was evaluated as ◯, and the elongation rate less than 65% was evaluated as x.
[0047] [Table 4]
[0048] As shown in Examples 13 to 17 in Table 4, in each of the items "stability of outer diameter dimension during high-speed extrusion", "heat resistance during extrusion", "pressure resistance during extrusion / after electron beam irradiation", and "degree of crosslinking", even when the conditions of the insulating layer were changed, all were evaluated as ◯. However, in the item of "heat aging test", the evaluation results of Examples 16 and 17 were ×. Examples 16 and 17 are examples in which electron beams are irradiated with high irradiation intensity. It was found that the degree of crosslinking can be improved by irradiating electron beams with high irradiation intensity, but a decrease in heat resistance can be confirmed. The value of the degree of crosslinking in Example 16 was 1.4 times the value of the degree of crosslinking in Example 15, and the value of the degree of crosslinking in Example 17 was 1.6 times the value of the degree of crosslinking in Example 15. From these results, when a cross-linking test is performed by irradiating the insulating layer 12 shown in FIG. 1 with an electron beam, it is preferable that the thickness of the insulating layer 12 covering the conductor 11 is 0.2 mm or less, and that the insulating layer 12 is cross-linked by irradiating it with an electron beam having an intensity of 5 Mrad or less.
[0049] The present invention is not limited to the above-described embodiment and examples, and various modifications can be made without departing from the spirit and scope of the present invention. [Industrial Applicability]
[0050] The present invention is applicable to wires and cables. [Explanation of symbols]
[0051] 10 Electric wire 11 Conductor 12 Insulating layer 20 Cable 21 Sheath (insulating layer)
Claims
1. A conductor; an insulating layer covering the conductor; having The insulating layer is For 100 parts by mass of polyvinyl chloride, 4 parts by mass or more of hydrotalcite; 0.03 parts by mass or more of polyethylene oxide and / or calcium laurate, 0.1 parts by mass or more of a phenolic antioxidant; A plasticizer; TMPT (trimethylolpropane triacrylate), Including, The phenolic antioxidant includes a phenolic antioxidant added to the plasticizer, An insulated wire, wherein a value obtained by dividing an amount of the phenol-based antioxidant added by an amount of the TMPT (trimethylolpropane triacrylate) added is 0.02 or less.
2. In claim 1, The insulating layer is Calcined clay, SiO 2 The content of Al 2 O 3 and clay with a content of more than The insulated wire further comprises:
3. In claim 2, Further comprising a black processed pigment, The black pigment comprises diisononyl phthalate (DINP).
4. In claim 1, The insulated wire further comprises a stearic acid-based metal soap in a total amount of 1 part by mass or more per 100 parts by mass of the polyvinyl chloride.
5. A method for producing an insulated wire having a conductor and an insulating layer covering the conductor, comprising the steps of: preparing a polyvinyl chloride resin composition containing, relative to 100 parts by mass of polyvinyl chloride, 4 parts by mass or more of hydrotalcite, 0.03 parts by mass or more of oxidized polyethylene and / or calcium laurate, 0.1 parts by mass or more of a phenolic antioxidant, a plasticizer, and TMPT (trimethylolpropane triacrylate), the phenolic antioxidant includes a phenolic antioxidant added to the plasticizer, and a value obtained by dividing the amount of the phenolic antioxidant added by the amount of TMPT (trimethylolpropane triacrylate) added is 0.02 or less; forming the insulating layer by extruding the polyvinyl chloride resin composition; A step of crosslinking the polyvinyl chloride resin composition by irradiating the insulating layer with an electron beam. A method for manufacturing insulated wire.
6. In claim 5, the step of crosslinking the polyvinyl chloride resin composition comprises irradiating the insulating layer with an electron beam having an intensity of 5 Mrad or less to crosslink the polyvinyl chloride resin composition.
Citation Information
Patent Citations
Vinyl chloride resin composition
JP1994032956A
Adhesive tape
JP2017119806A
Vinyl chloride resin composition, insulated wire, cable, method for producing insulated wire, and method for producing cable
JP2020186286A
Surface-treated hydrotalcite and polyvinyl chloride resin composition containing it
JP2003040614A